The Dynamin Chemical Inhibitor Dynasore Impairs Cholesterol Trafficking and Sterol-Sensitive Genes Transcription in Human HeLa Cells and Macrophages - Girard, Emmanuelle; Paul, Jean Louis; Fournier, Natalie; Beaune, Philippe; Johannes, Ludger; Lamaze, Christophe; Védie, Benoît (PLOS ONE, 2011)
Intracellular transport of cholesterol contributes to the regulation of cellular cholesterol homeostasis by mechanisms that are yet poorly defined. In this study, we characterized the impact of dynasore, a recently described drug that specifically inhibits the enzymatic activity of dynamin, a GTPase regulating receptor endocytosis and cholesterol trafficking. Dynasore strongly inhibited the uptake of low-density lipoprotein (LDL) in HeLa cells, and to a lower extent in human macrophages. In both cell types, dynasore treatment led to the abnormal accumulation of LDL and free cholesterol (FC) within the endolysosomal network. The measure of cholesterol esters (CE) further showed that the delivery of regulatory cholesterol to the endoplasmic reticulum (ER) was deficient. This resulted in the inhibition of the transcriptional control of the three major sterol-sensitive genes, sterol-regulatory element binding protein 2 (SREBP-2), 3-hydroxy-3-methyl-coenzymeA reductase (HMGCoAR), and low-density lipoprotein receptor (LDLR). The sequestration of cholesterol in the endolysosomal compartment impaired both the active and passive cholesterol efflux in HMDM. Our data further illustrate the importance of membrane trafficking in cholesterol homeostasis and validate dynasore as a new pharmacological tool to study the intracellular transport of cholesterol.